2022
DOI: 10.1039/d2ra02581g
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of bacterioruberin and proteins using aqueous solutions of surface-active compounds

Abstract: Bacterioruberin and proteins were recovered from a marine bacterium by using aqueous solutions of surface-active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…By analyzing the trend of AcA, ButA, and DecA, it is possible to infer that the elongation of the carbon chain lowered the extraction success. This is somewhat unexpected given the reported extraction of bacterioruberin from H. mediterranei using aqueous solutions of anionic or neutral surfactants, albeit at a lower concentration of 250 mM …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…By analyzing the trend of AcA, ButA, and DecA, it is possible to infer that the elongation of the carbon chain lowered the extraction success. This is somewhat unexpected given the reported extraction of bacterioruberin from H. mediterranei using aqueous solutions of anionic or neutral surfactants, albeit at a lower concentration of 250 mM …”
Section: Resultsmentioning
confidence: 99%
“…A bacterioruberin yield of extraction of 4.74 ± 0.01 mg bacterioruberin g wet biomass –1 was obtained experimentally, encompassing a mean relative deviation of 2.61%. Finally, an optimal point was chosen at the following operational conditions (110.4 min, 0.5 × Ment, and SLR 0.1), achieving a maximum yield of 5.16 ± 0.01 mg bacterioruberin g wet biomass –1 (see Table S2) This represents a significant increase relative to the obtained extraction yields using pure ethanol (0.76 mg bacterioruberin g wet biomass –1 ) and aqueous solutions of nonionic surfactants (0.37 mg bacterioruberin g wet biomass –1 ) . Moreover, the Ment:LevA eutectic was extensively characterized by Wils et al and was shown to be biocompatible with human epidermal keratinocytes below concentrations of 200 μg mL –1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations